Emotions experienced by instructors delivering written feedback and dialogic feed-forward - Hill, Jennifer; Berlin, Kathy; Choate, Julia; Cravens-Brown, Lisa; McKendrick-Calder, Lisa; Smith, Susan (My University, 2023)
Understanding the emotions experienced by higher education instructors related to assessment feedback, how instructors understand student emotions, and how instructors might manage these emotions positively, can help to secure the educational benefits of feedback. In this research, we aimed to explore the emotional responses that instructors experienced through the giving and receiving of assessment feedback. We undertook qualitative data collection, carrying out individual semi-structured interviews with instructors from three universities who had administered a dialogic feed-forward intervention on one of their teaching units. The full interview transcripts were analysed inductively using thematic analysis. Five main themes emerged from the interview data: 1. Summative written feedback aroused largely negative emotions in instructors because they felt distanced from their students; 2. Instructors experienced a broad range of emotions related to dialogic feed-forward encounters, emerging from their proximity to students; 3. Dialogic feed-forward, as an affective encounter, was emotionally challenging for instructors; 4. Dialogic feed-forward built strong learning relationships between students and instructors, strengthening students’ sense of belonging; 5. Dialogic feed-forward was transformational for instructors as educators. We consider the implications of our findings for instructors and wider assessment and feedback practices, including emotional labour, promotional reward, and instructor professional development.
Keywords: assessment feedback; dialogic feed-forward; emotions; feedback literacy; emotional labour